ANALYSIS OF A THERMAL-PROTOVOLTAIC SYSTEM WITH GLYCERIN-BASED PHASE CHANGE MATERIAL EMPLOYED IN CURITIBA - Rosa, Danniella; Antonio Bertogna, Marco; José Jerônimo de Santana Ponte, Maria; Viriato Coelho Vargas, Jose; Hennings Och, Stephan (Revista de Engenharia Térmica, 2025)
Electrical energy from solar energy has risen in the last few decades. When using photovoltaic cells for this transformation, it was found their efficiency is low compared to traditional sources. The efficiency peaks at 19.2% for polycrystalline silicon modules and 22.9% for monocrystalline ones. These low values are a result of the Shockley–Queisser limit. The heating cells reduces that efficiency in 0.4%/°C in crystalline silicon panels. This study has the objective of analyzing different variations of a hybrid photovoltaic-thermal (PVT) system with a phase change material (PCM). The chosen configurations are: standard hybrid PVT system with the passage of water below the panel; hybrid PVT system with PCM (glycerin) reservoir below it and the thermal water system at the bottom (PVT+PCM); hybrid PCM an inversion of the cooling systems, with the water placed above the PCM reservoir (PVT+PCM-I). Tests were conducted in the city of Curitiba-PR for. A mathematical model utilizing the least-square method was made. After analyzing the PVT+PCM-I had temperature reduction than the other two. In all cases, the variation of the open circuit tension mirrors the variation in temperature: as the temperature increases, the tension is reduced. The mathematical model showed itself coherent for all cases.